Carcass and physical meat characteristics of thin tail sheep (TTS) based on calpastatin gene (CAST) (Locus intron 5 â exon 6) genotypes variation - Dagong, Muhammad Ihsan Andi; Herman, R; Sumantri, C; Noor, R.R; Yamin, M (Indonesian Animal Sciences Society, 2012)
The quality of sheep carcass is mostly determined by the total lean meat production, meat distribution on the carcass and the quality of meat. Calpastatin gene (CAST) is known to have an association with carcass and meat quality traits. The objective of this research was to identify the association between CAST polymorphisms and carcass characteristics in Thin Tail Sheep (TTS). Thirty three heads of sheep representing three genotypes of CAST (CAST-11, CAST-12 and CAST-22) were identified for carcass and meat characterisation. There was no significant difference between CAST polymorphisms with meat tenderness, pH, water holding capacity and cooking loss, neither with carcass weight and dressing percentage among genotypes. Shoulder proportion of CAST-11 genotype was larger than that of CAST-12 or CAST-22, but the lean meat proportion of CAST-22 genotype in shoulder, rack and loin were higher than those of CAST-11 but not different from CAST-12. The fat percentage of CAST-11 was the highest among the genotypes. CAST-22 genotype has higher lean meat percentage than the CAST-11. Variation in CAST gene could be used as marker assisted selection in sheep for higher lean meat proportion. Key Words: Calpastatin, Polymorphisms, Carcass Characteristics, Meat Quality, Thin Tail Sheep